Social Challenges of Industrial Relations: A Study of Federal Polytechnic Oil and Gas, Bonny, Rivers State, Nigeria - Nwachukwu Precious Ikechukwu; Aroh Grace Onyekachi; Tamuno, Daniel Achori (International Journal of Engineering and Management Research, 2019)
The purpose of this paper was to investigate the social challenges of Industrial Relations in Federal Polytechnic Oil and Gas, Bonny, Rivers State, Nigeria and to evaluate the different Industrial Relations which were carried out in most organizations. The research design was descriptive survey to investigation and observed the proper Industrial Relations Practices which were carried out in Oil and Gas companies operating in the Bonny, Rivers State, Nigeria. It very important for companies to avoid societal conflicts and discontents, ensure industrial peace and harmony, as a result of achieving better performance, at work place which encourage productivity and growth. Human being are the active agents who accumulate capital, exploit natural resources, build social, economical and political organizations and carry forward national development.